2021
DOI: 10.1093/occmed/kqab043
|View full text |Cite
|
Sign up to set email alerts
|

Persistent post-covid symptoms in healthcare workers

Abstract: Background Recent reports suggest a higher incidence of COVID-19 infections among healthcare workers (HCW). However, information about the long-term complications affecting this population is lacking. Aims Investigation of long-term impact of COVID-19 in HCW. Methods Seropositivity for SARS-CoV-2 antibodies was evaluated for the majority of HCW in an English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 7 publications
3
81
1
4
Order By: Relevance
“…[ 18 19 20 ] Fatigue and dyspnea as the predominant post COVID symptoms have been reported from multiple studies as seen in our study also. [ 18 20 21 ]…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[ 18 19 20 ] Fatigue and dyspnea as the predominant post COVID symptoms have been reported from multiple studies as seen in our study also. [ 18 20 21 ]…”
Section: Discussionsupporting
confidence: 82%
“…Higher percentage of post COVID symptoms was observed in Italy (87%), Spain (62%) while a study from England reported only 32% of HCW reporting persistence of any one symptom. [ 18 19 20 ] Fatigue and dyspnea as the predominant post COVID symptoms have been reported from multiple studies as seen in our study also. [ 18 20 21 ]…”
Section: Discussionsupporting
confidence: 82%
“…Out of 3759 HW tested, 932 (24%) were infected with SARS-CoV-2. After three to four months, 39% still reported severe fatigue and 40% reported mild to moderate shortness of breath [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The idea that SARS-CoV-2 infection could be associated with long-term health outcomes first appeared in the literature in mid-2020 [11], along with previous evidence of longhaul symptoms following the Ebola [12] virus outbreak and infections from previous coronaviruses [13,14]. COVID-19 survivors have been shown to experience a constellation of symptoms such as fatigue, dyspnea or breathlessness [8,15], palpitations [16,17], brain fog, lack of concentration [18,19], sleep disturbances (i.e., insomnia) [20], headache [17,[21][22][23][24][25], orthostatic intolerance [25], anxiety and post-traumatic stress disorder [20,23,[26][27][28], chest pain, joint pain [8], sore throat [17], and hair loss [15] persisting >4 weeks after recovery. These clinical sequelae share similarities with post-acute symptoms reported after severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) epidemics, caused by previous coronaviruses [14].…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 99%